Electrohypersensitivity: what is belief and what is known? - de Vocht, Frank; Röösli, Martin (Frontiers in Public Health, 2025)
Electrohypersensitivity (EHS), or idiopathic environmental intolerance attributed to electromagnetic fields (IEI-EMF), is a condition with fluid and transient symptoms associated to exposure to non-ionizing radiation by people claiming to suffer from it. However, the scientific evidence linking the exposure to the reported effects to datwe has eluded researchers, and may not even exist. In the current perspective we outline what is objectively known about EMF as the cause for EHS and what is based on anecdotal information only. We discuss why randomized provocation trials were considered the most appropriate research methodology to elucidate causal links between EMF exposure and effects in a scientifically robust manner, what the main arguments against such studies are, and whether these criticisms are valid. Finally, we synthesize the evidence and beliefs around EHS and provide future directions of research and practice.